Reducing outpatient waiting time with a simulated queuing model - Lim, Lionel Guo Liang. (2010)
In an effort to stay competitive with each other, hospitals in Singapore are constantly looking into avenues to improve the level of their service quality. This is especially important, in view of the aging population, which is the main cause for the increasing demand for healthcare services. One of the major issues faced by hospitals is that of the prolonged waiting time experienced by patients seeking treatment, regardless of department or specialist clinic. Thus, in an effort to help reduce patient waiting time in the hospital, a study has been done on the patient flow process of a Specialist Outpatient Clinic in Tan Tock Seng Hospital.